1998
DOI: 10.1038/sj.onc.1202247
|View full text |Cite
|
Sign up to set email alerts
|

EB1, a protein which interacts with the APC tumour suppressor, is associated with the microtubule cytoskeleton throughout the cell cycle

Abstract: The characteristics of the adenomatous polyposis coli (APC) associated protein EB1 were examined in mammalian cells. By immunocytochemistry EB1 was shown to be closely associated with the microtubule cytoskeleton throughout the cell cycle. In interphase cells EB1 was associated with microtubules along their full length but was often particularly concentrated at their tips. During early mitosis, EB1 was localized to separating centrosomes and associated microtubules, while at metaphase it was associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
197
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 9 publications
14
197
0
3
Order By: Relevance
“…Immuno¯uorescence analysis demonstrated that EB1 in HCT116 cells was associated with the microtubule cytoskeleton throughout the cell cycle (results not shown), as previously shown by ourselves (Morrison et al, 1998a) in a variety of other cell types. Furthermore, Western blotting of PBS/TX100 solubilized HCT116 cell extracts con®rmed that a single, completely soluble EB1 species was expressed in these cells (results not shown).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Immuno¯uorescence analysis demonstrated that EB1 in HCT116 cells was associated with the microtubule cytoskeleton throughout the cell cycle (results not shown), as previously shown by ourselves (Morrison et al, 1998a) in a variety of other cell types. Furthermore, Western blotting of PBS/TX100 solubilized HCT116 cell extracts con®rmed that a single, completely soluble EB1 species was expressed in these cells (results not shown).…”
Section: Resultssupporting
confidence: 82%
“…EB1 was detected in all three precipitates. b-catenin was detected in precipitates from AS or G1-S arrested cells, with slightly more seen in G1-S extracts, but little was detected in precipitates from G2-M arrested cells Morrison et al, 1998a). This experiment demonstrates that the interaction between APC and EB1 does not require both proteins to be associated with microtubules, or indeed the presence of an intact microtubule cytoskeleton.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations